The importance of independent income: Understanding the role of non-means-tested earnings replacement benefits - Fran Bennett; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We argue that independent entitlement to income is important. This implies that earnings replacement benefits paid to individuals fulfil a range of functions which means-tested benefits, assessed at the family rather than individual level, cannot. The argument also highlights the need to consider gender differences in the receipt of income. We explore the implications of a scenario in which non-means-tested earnings replacement benefits are abolished and means-tested benefits and tax credits fill some of the gap. This illustrates the effects of UK trends and in proposals for further reform - in the decline in non-means-tested benefits and the increase in means testing - taken to their ultimate conclusion.
Keywords: D31; I38; 330; Income; Benefits; Means testing; Gender; Einkommen; Haushaltseinkommen; Lohnersatzleistungen; Steuerbegünstigung; Geschlechterdiskriminierung; Großbritannien